Enantioselective analysis of the pesticide imazamox after in vitro permeability study in Caco-2 cells - Serpellone, Carolina Oliveira; Barbetta, Maike Felipe Santos; Perovani, Icaro Salgado; Ballestero, Giulia; de Albuquerque, Nayara Cristina Perez; de Oliveira, Anderson Rodrigo Moraes [UNESP] (Wiley, 2024)
Imazamox (IMX), a chiral herbicide used in cereals and oilseed crops to control weeds, is commonly sold as a racemic mixture. Its enantiomers, being chiral compounds, may exhibit unique properties when exposed to chiral environments. While IMX enantiomers have been reported to degrade differently in soil and be toxic to some species, their effects on human systems remain poorly understood. This study utilized Caco-2 (human colon adenocarcinoma cell line) cells to assess the in vitro permeability of a racemic mixture of IMX and its isolated enantiomers. Additionally, the study aimed to evaluate whether the metabolite imazamox-O-desmethyl (IMX-D) forms during the permeability process. An enantioselective chromatographic method was developed, fully validated, and the apparent permeability values were obtained. The apparent permeability of rac-IMX, (+)-IMX, and (−)-IMX was determined to be 4.15 × 10–5, 5.78 × 10–5, and 7.33 × 10–5cm s–1, respectively. These findings suggest that IMX exhibits high intestinal permeability, with an enantioselective absorption for (–)-IMX as compared to (+)-IMX. Finally, the permeability study in Caco-2 cells revealed that the metabolite IMX-D was not generated.
Keywords: Caco-2 cells; chiral HPLC; imazamox; permeability; pesticide